1920
DOI: 10.5962/bhl.title.16800
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Myxosporidia; a synopsis of genera and species of Myxosporidia; with 25 plates and 2 textfigures, by Rokusaburo Kudo ...

Abstract: The total number of species of Myxosporidia reported up to date and described in the following pages, excluding 12 ambiguous forms, reaches 237 of which 125 are species which have been observed since 1910.* The distribution of these new forms is as follows: Africa 6 species Asia 23 species Australia 1 species Europe 31 species North America 63 species South America 1 species Thus, the majority of the species were observed in other lands than Europe, nearly half being recorded from North American waters. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 1 publication
5
71
0
Order By: Relevance
“…According to our knowledge 11 species (Table 1) belonging to the Myxobolus genus have been described infecting Mugil cephalus (Kudo 1920, Shulman 1966, Iversen et al 1971, Landsberg & Lom 1991, Lom & Dykova 1992, 1994. Most of them can be clearly distinguished from each other.…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge 11 species (Table 1) belonging to the Myxobolus genus have been described infecting Mugil cephalus (Kudo 1920, Shulman 1966, Iversen et al 1971, Landsberg & Lom 1991, Lom & Dykova 1992, 1994. Most of them can be clearly distinguished from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Transelectromicroscopic studies by Kaup et al (1995) confirmed the histological observations that the monosporic sporoblasts of S. molnari surrounded by an envelope cell lay isolated in the gill epithelium. Before 1983, S. molnari was identified as S. carassii; thereafter, it was distinguished from S. carassii Kudo, 1919 andS. chinensis Lom, Dyková, Pavlásková andGrupcheva, 1983 based on spore morphology, host species and geographic locality (Lom et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Only the length (11 µm) and width (7 µm) of the spores were initially described for this species, which has polar capsules of unequal size (GURLEY 1893). Later, spores of 5.2 µm in length by 3.3 µm in width were reported for this species, along with the hosts, Piramutana blochi (= Corydoras blochi Nijssen, 1971) and Synodontis schall (Bloch & Schneider, 1801) from the same locality (KUDO 1920). According to PINTO (1928) P. blochi referred as Pimelodus clarias (Bloch, 1782), while S. schall occurs only in the River Nile in Africa according to M. colossomatis*** 11.8 (11.4-11.2) 6.9 (6.6-7.2) 3.7 (3.5-4.0) 6.0 (5.8-6.6) 2.1 (1.…”
Section: Figs 1-4mentioning
confidence: 99%